2016
DOI: 10.1111/eea.12513
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying rates of random mating in western corn rootworm emerging from Cry3Bb1‐expressing and refuge maize in field cages

Abstract: The western corn rootworm (WCR), Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), is the most significant pest of field maize, Zea mays L. (Poaceae), in the USA. Maize plants expressing Bt toxins targeting the corn rootworm complex have been widely adopted and are the primary insecticidal control measure for this pest in North America. Insect resistance management tactics using various refuge structures have been adopted to ensure Bt products will retain durability. An assumption of the refu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…In our 2014 study using natural populations and field cages, we found that non‐random mating occurred in seed blend and strip refuges . Our current results support these findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our 2014 study using natural populations and field cages, we found that non‐random mating occurred in seed blend and strip refuges . Our current results support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…amount over the average for known unenriched samples) was used to identify beetles that fed as larvae primarily on 15 N‐treated refuge plants. A series of calculations was used to determine the amount of 15 N in excess for each sample . The Purdue Stable Isotope Laboratory recommends that an excess % 15 N > 0.5 be used as a threshold for identifying enriched samples.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations